Does Client Complexity Before and During the Covid-19 Pandemic Affect Audit Partner Independence? Evidence from the Modified Audit Opinions - Amabel, Vania; Herusetya, Antonius (Universitas Pelita Harapan, 2023)
This study examines the impact of the client's level of complexity on the modified audit opinion (MAO). This study also examines the moderating effect of the COVID-19 pandemic on the relationship between client complexity level and modified audit opinion. The level of client complexity is measured using a complexity score with the dimensions of company size, level of bankruptcy risk, level of company growth, and financial performance. The study sample was taken from all listed companies on the Indonesia Stock Exchange except for the financial industry, with an observation period of 2018-2020. Using logistic regression analysis and 1020 firm-year observations, our study found that client complexity positively affects the audit partner quality measured by the tendency to issue modified audit opinions. Further study found no evidence that the COVID-19 pandemic occurred in 2020 has a moderating effect on the relationship between client complexity and modified audit opinions. This study's results imply that the sample profile, which the Big Four audit firms dominate, reflects the relatively high quality of audit partners in Indonesia in issuing modified audit opinions despite client complexities.